A woman's dilemma : Mercy Otis Warren and the American Revolution - Zagarri, Rosemarie, 1957- (John Wiley & Sons Inc., 2015)
"The second edition of A Woman's Dilemma: Mercy Otis Warren and the American Revolution updates Rosemarie Zagarri's biography of one of the most accomplished women of the Revolutionary era. The work places Warren into the social and political context in which she lived and examines the impact of Warren's writings on Revolutionary politics and the status of women in early America. Presents readers with an engaging and accessible historical biography of an accomplished literary and political figure of the Revolutionary era Provides an incisive narrative of the social and intellectual forces that contributed to the coming of the American Revolution Features a variety of updates, including an in-depth Bibliographical Essay, multiple illustrations, a timeline of Warren's life, and chapter-end study questions Includes expanded coverage of women during the Revolutionary Era and the Early American Republic "--